The impact of principals’ transformational leadership and school climate on teacher achievement motivation in public elementary schools - Br Nainggolan, Rindah; Hadiyanto, Hadiyanto; Nellitawati, Nellitawati; Sabandi , Ahmad (Universitas Jambi, Indonesia, 2026)
This research aimed to examine the contributions of principals' transformational leadership and school climate to teacher achievement motivation, as well as the combined effects of these factors in public elementary schools in the Mentawai Islands Regency. This research used a quantitative method with a population of 181 teachers. The sample was drawn using stratified proportional random sampling, totaling 65 teachers. The research instrument used a questionnaire. Furthermore, the results indicate that the principal's transformational leadership significantly contributes to public elementary school teachers' achievement motivation in the Mentawai Islands Regency, accounting for 78.6% of the variance. In comparison, the school climate contributes 5.7%. Additionally, both the principal's transformational leadership and the school climate together contribute 46% to these teachers' achievement motivation. These indicate that the hypothesis can be accepted empirically.